Układ przestrzenny a konkurencyjność regionów - analiza ilościowa - Markowska-Przybyła, Urszula (Spatial System Versus Regions Competitiveness - Quantitative Analysis, 2005)
This paper discusses the relation between the spatial structure of territory and its competitiveness. The author determines the degree of connection of four components of region's space (i.e.: households (structure of settlement), economic zone, socio-economic infrastructure and the environment) with the competitiveness of these regions. Analyses were made with special emphasis laid on Lower Silesia.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 195-216